UV radiation theory and the Lynn (2010): Italian debate - León Eyzaguirre, Federico R. (2017)
Lynn’s (2010) attribution of decreasing north-to-south PISA scores and GDP in Italy to inherited intelligence caused debate, but cognitive-capitalism’s tenet that regional/national intelligence, inherited or not, determines provincial/country wealth remains unchallenged. We introduce a new theory into the debate and test a UV radiation → intelligence → socioeconomic latent variable (SELV) model vis-à-vis a radiation → SELV → intelligence one. Only the latter is found well-adjusted in Italy, more so among adolescents than children. Since hair and eye color vary with latitude in Italy and UV radiation could be a proxy for ancestry, the models are retested among White students in the USA. Similar results observed suggest that, in both countries, increased UV radiation impairs socio-economic development, perhaps by reducing industriousness through oxidative stress. The ensuing less-developed social environments exert negative influences on individuals’ cognition. Yet, ancestry appears to add latitudinal socioeconomic variance in Italy. A third study in Brazil, in turn, shows that cognitive effects of UV radiation through SELV are clearly distinguishable from the cognitive effects of race. The results suggest that the postulate that intelligence causes wealth needs revision.